Analysis of the Infuence of Sewaco, Platforms and Bases on the Operational Capability of Submarines - Haryanto A.R, Timbul; Octavian, A.; Bura, Romie O. (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Indonesia is an archipelagic country whose territory lies in a cross position between two continents and two oceans. The position of the centre of gravity owned by Indonesia makes the security level decrease to threaten Indonesia's sovereignty. The increasing escalation in the South China Sea area, marked by many manoeuvres of foreign warships from significant countries, does not rule out the possibility that submarines from foreign countries will participate in showing their war power. Faced with the vulnerabilities in Indonesia's territorial waters and the quantity of ownership of existing warships, especially submarines, it is necessary to research them. The hypothesis in this study is that if the capability of the rental co, platform and base increases, it will increase the operational capability of the submarine. The methodology used is descriptive quantitative using SPSS 25 software and Microsoft Excel 2013 with multivariate correlation data analysis techniques. The influence of the rental co, platform and base on the operational capability of the submarine is 59.8%. So that several factors that affect the submarine's ability to carry out operations are the rental co, platforms, and base facilities owned. These factors must be improved to carry out everyday operational tasks continuously.